Analiza sprememb kmetijske rabe na območjih okoljsko občutljivega trajnega travinja med letoma 2023 in 2024 - Kosor, Nastja (Varstvo narave, 2025)
We analysed changes in the agricultural use of permanent grassland (1300) within EnvironmentallySensitive Permanent Grassland areas (ESPG). We compared data for 2023 and 2024, when Regulation (EU) 2024/1468 (2024) and the Regulation on Cross-Compliance Rules (Official Gazette of the Republic of Slovenia, No. 2/24 with amendments) introduced certain exceptions or exclusion criteria for the implementation of ESPG. The results show that as much as 170 hectares of permanent grassland were ploughed in ESPG areas during this period. Ploughing also took place in protected areas and areas where European endangered species are present, such as corncrake (Crex crex), scarce large blue (Phengaris teleius) and dusky large blue (Phengaris nausithous). There were significantly fewer changes in Natura 2000 areas without ESPG status, which confirms the usefulness of designating ESPG areas. Nevertheless, the analysis shows that the current method of implementing ESPG does not ensure effective protection of grasslands in accordance with the provisions of Directive 2009/147/EC of the European Parliament and of the Council of 30/11/2009 on the conservation of wild birds and Council Directive 92/43/EEC of 21/05/1992 on the conservation of natural habitats and wild fauna and flora.
Keywords: agricultural policy; change of use; endangered species; ESPG; exclusion criteria; GERK; habitat protection; izločitvena merila; kmetijska politika; Natura 2000; ogrožene vrste; OOTT; permanent grasslands; plowing; preoravanje; sprememba rabe; trajni travniki; varstvo habitatov